School Alert Application: Parent-Teacher Engagement System - Tan, Wan Ying; Ibrahim, Rosziati (Applied Information Technology And Computer Science, 2024)
The School Alert Android application is designed for busy parents of SJI International School to stay informed about their children and the school. It also provides a web-based system for teachers to manage the system. A simple Software Development Life Cycle (SDLC) model is implemented throughout software development. The system consists of ten modules, including login, registration, class management, user management, student information, attendance, academic performance, financial management, activities and messaging. Android Studio and Java are used for mobile development, while web technologies like HTML, PHP, and MySQL are used for the administrative website. The system then undergoes acceptance testing and functionality testing to ensure its effectiveness. The goal is to enhance parent-teacher engagement and improve student performance. Future enhancements may include notification feature of the latest news for all the system’s module.